The teaching process trhough social networks: towards a new model or style of teaching - Mateos-Aparicio Palacios, Miguel (Estudios sobre el Mensaje Periodístico, 2012)
The use of social networks for the educational field opens new ways of investigation, because of the many possibilities in communication, interaction and socialization that they offer, as well as for the variety of resources and tools for the teaching and learning process, although they are, essentially, informal environments whose dynamics of action is far from the systems of the formal education control. This article shows a part of a final thesis report that focused on the educational use of social networks. In particular, it deals with aspects related to the teaching process, as the teacher´s role, the teaching models and possible curriculum approaches that social networks can offer. For this, we study the case “Econogargallo”.